2017
DOI: 10.1186/s12872-017-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Findings of transoesophageal echocardiogram in appropriately anticoagulated patients with persistent atrial fibrillation prior to planned cardioversion

Abstract: BackgroundTo evaluate a diagnostic value of transoesophageal echocardiogram (TEE) in appropriately anticoagulated patients with a non-valvular atrial fibrillation (AF) and to establish possible additional indications for TEE; to evaluate the incidence of left atrial (LA) thrombi in appropriately anticoagulated patients in daily clinical practice.MethodsThis retrospective study analyses data of 432 patients who had been anticoagulated by means of oral anticoagulants (OACs) prior to planned cardioversion during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The overall incidence of thrombus formation in our study was 4.7%. Patients without anticoagulation therapy showed highest incidence (9.5%), whereas patients under anticoagulation therapy had a lower but still remarkable rate (4.1%) being in line with findings from recent studies . We observed an apparently significant difference in the overall incidence of thrombus formation between NOAC‐ and VKA‐treated patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall incidence of thrombus formation in our study was 4.7%. Patients without anticoagulation therapy showed highest incidence (9.5%), whereas patients under anticoagulation therapy had a lower but still remarkable rate (4.1%) being in line with findings from recent studies . We observed an apparently significant difference in the overall incidence of thrombus formation between NOAC‐ and VKA‐treated patients.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study addressing the question of factors influencing thrombus formation in patients with appropriate OAC scheduled for cardioversion, thrombi were detected in 5.8% of patients (VKA and NOAC), a rate twice as high as our findings . These patients were noted to show a higher rate of impaired LV‐function and higher CHA 2 DS 2 ‐VASc‐Scores (≥5).…”
Section: Discussionsupporting
confidence: 49%
“…Some studies have found the CHADS 2 and CHA 2 DS 2 -VASc scores to be the strongest predictors of LAAT prior to electrical cardioversion [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported slightly lower and higher rates of LAT in patients scheduled for ECV of AF. However, most of these studies are single-centre retrospective cohorts or had low numbers of patients 5–8 , 13 , 14 . Other randomized trials—such as the ACUTE trial, which enrolled 1222 patients with AF for ECV—included 549 patients who underwent TOE prior to ECV and found a higher rate of LAT (13.8%) 15 .…”
Section: Discussionmentioning
confidence: 99%